A63 REFINING THE CANADIAN ASSOCIATION OF GASTROENTEROLOGY GUIDELINE ON SCREENING IN PERSONS WITH A FAMILY HISTORY OF NONHEREDITARY COLORECTAL CANCER OR ADENOMA: A MODIFIED DELPHI PROCESS. (4th March 2021) - Tinmouth, J; Paramalingam, A; Bellini, A; Cotterchio, M; Dekker, E; Doctorow, R; Hassan, C; Haddad, E; Lofters, A; MacIntosh, D; Martin, J; McCurdy, B; et al.
Abstract: Background: In 2018, the Canadian Association of Gastroenterology (CAG) published an extensive systematic review and guideline on screening in persons with a family history (FHx) of nonhereditary colorectal cancer (CRC) and adenoma. While CAG's recommendations were evidence-based, some recommendations lacked precision (e.g. ranges for some start ages & intervals) and screening cessation age was not addressed, leading to implementation challenges for practitioners and CRC screening programs. Aims: To review and update the evidence since the 2018 guideline and to formulate implementable recommendations in the Ontario context that are aligned with the CAG guideline. Methods: ColonCancerCheck (Ontario's organized CRC screening program) conducted a modified version of the literature search used by CAG (Jan 2017 - Sept 2019). A 19-member expert panel with Canadian and international representatives from endoscopy, primary care, epidemiology, organized CRC screening programs, Ontario's cancer system and the general public refined the recommendations of the CAG guideline for the purposes of implementation in an organized CRC screening program using a modified Delphi process. This iterative process involved a series of webinars and anonymous survey rounds where the panel reviewed evidence materials and provided online feedback to develop, refine & achieve consensus on screening recommendations in persons with a FHx of CRC/adenoma. Consensus was achieved if ≥75% of members agreed or strongly agreed with the statement. Results: Six new systematic reviews and 2 new guidelines were identified. New evidence included data on the absolute risk (10 year & lifetime risk) of CRC by type of FHx, as well as the performance of fecal immunochemical testing (FIT) and barriers to CRC screening in persons with a FHx of CRC. The expert panel participated in 3 webinars and 4 online surveys to arrive at consensus. Panel recommendations and level of consensus will be reported for the 6 statements (Table). Conclusions: Building from the CAG guideline, we derived evidence-based and implementable recommendations for screening persons with a FHx of CRC or adenoma. Funding Agencies: Ontario Health (Cancer Care Ontario)